Myocyte [Na+]i Dysregulation in Heart Failure and Diabetic Cardiomyopathy - Despa, Sanda (Frontiers in Physiology, 2018)
By controlling the function of various sarcolemmal and mitochondrial ion transporters, intracellular Na+ concentration ([Na+]i) regulates Ca2+ cycling, electrical activity, the matching of energy supply and demand, and oxidative stress in cardiac myocytes. Thus, maintenance of myocyte Na+ homeostasis is vital for preserving the electrical and contractile activity of the heart. [Na+]i is set by the balance between the passive Na+ entry through numerous pathways and the pumping of Na+ out of the cell by the Na+/K+-ATPase. This equilibrium is perturbed in heart failure, resulting in higher [Na+]i. More recent studies have revealed that [Na+]i is also increased in myocytes from diabetic hearts. Elevated [Na+]i causes oxidative stress and augments the sarcoplasmic reticulum Ca2+ leak, thus amplifying the risk for arrhythmias and promoting heart dysfunction. This mini-review compares and contrasts the alterations in Na+ extrusion and/or Na+ uptake that underlie the [Na+]i increase in heart failure and diabetes, with a particular emphasis on the emerging role of Na+ - glucose cotransporters in the diabetic heart.